ПРО НЕОБХІДНІСТЬ РОЗВИТКУ І ПОШИРЕННЯ ОСНОВ МОРАЛЬНОГО ЛІДЕРСТВА В ПРАКТИЦІ ВІТЧИЗНЯНОГО ПУБЛІЧНОГО УПРАВЛІННЯ І АДМІНІСТРУВАННЯ - Дзвінчук Д. І.,; Лютий М. О.,; Лютий О. В.,; Петренко В. П., (International Journal of Innovative Technologies in Social Science, 2019)
The article demonstrates that, despite certain achievements of the national management science in theory and practice of leadership in the field of public management and administration, the results of the practical use of these recommendations in the management of the state remain unsatisfactory. The authors prove that the main reason is the unsatisfactory state of the morality and integrity of most managers - leaders of the system of public management and administration, since there are no corresponding requirements and examinations of applicants in the processes and technologies of personnel selection of the system based on the above mentioned characteristics. Taking into account the existing world practice of using test instruments to determine the level of morality and integrity of the applicants, it is proposed to supplement the process of selecting candidates for entry into the civil service by making them pass obligatory tests on morality and ability for moral leadership, intensifying the process of training applicants on the basis of intellectualization using modified authors of the leadership model, which will provide the leader's ability to effectively use both their own intellect and intellect of their followers.